Comparative study of Deferiprone versus Deferiprone with Deferasirox as iron chelation therapy in Thalassemic children (Bangladesh Journal of Child Health, 2020)
Background: Combination therapy of Deferiprone (DFP) with Deferasirox (DFX) is an efficacious and safe modality to reduce serum ferritin in multi-transfused children with thalassemia.Objectives: To compare the efficacy of Deferiprone versus Deferiprone with Deferasirox as iron chelation therapy of transfusion dependent thalassemia children.Materials and Methods: A non-randomized control clinical trial was done in department of Pediatric Hematology and Oncology, Dhaka Medical College Hospital and Bangladesh Thalassemia Hospital in Dhaka during the period of October 2016 to September 2017. Thirty children with transfusion dependent thalassemia major between 3 to 12 years of age were included in each group in this study. Children with thalassemia minor, after splenectomy, with comorbidities and on other iron chelation therapy were excluded from this study.Results: Among total enrolled 60 cases in this study, initial mean serum ferritin level was 3397.48 ± 774.48 ng/ml in DFP-monotherapy group and 3413.70 ± 1114.05ng/ ml in DFP-DFX combination group. Mean serum ferritin level at 6thmonth was found 2730.63 ± 839.91ng/ml in DFP-monotherapy group and 1654.20 ± 934.90 ng/ml in DFP-DFX-combination group which shows rapid reduction of serum ferritin level in DFP-DFX-combination group. 12 (40.0%) patients had arthralgia in DFPmonotherapy group and 5(16.7%) patients had vomiting in DFP-DFX-combination group. No abnormalities seen in liver and renal function tests.Conclusion: Combination therapy with Deferiprone and Deferasirox is more effective in reduction of iron overload and drug related complications in transfusion dependent thalassemia patients.Bangladesh J Child Health 2019; VOL 43 (3) :152-156